f(-1)+f(2)=2(-1)-3+2(2)-3

Simple and best practice solution for f(-1)+f(2)=2(-1)-3+2(2)-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f(-1)+f(2)=2(-1)-3+2(2)-3 equation:



f(-1)+f(2)=2(-1)-3+2(2)-3
We move all terms to the left:
f(-1)+f(2)-(2(-1)-3+2(2)-3)=0
We add all the numbers together, and all the variables
f^2+f(-1)-14=0
We multiply parentheses
f^2-1f-14=0
a = 1; b = -1; c = -14;
Δ = b2-4ac
Δ = -12-4·1·(-14)
Δ = 57
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$f_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$f_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$f_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-1)-\sqrt{57}}{2*1}=\frac{1-\sqrt{57}}{2} $
$f_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-1)+\sqrt{57}}{2*1}=\frac{1+\sqrt{57}}{2} $

See similar equations:

| 3*c=-18 | | 5x+3+90=8x-4 | | 2(10+4x)=60 | | 13-3x+10=5(x-11)-6 | | -2(7-y)+4=14 | | −3(n+2)−5=−23. | | 4(2x-8)=-12 | | 4p-9=3p+23+9 | | 7(b+3)=1+7b-(-4) | | 4/3)c+1=(5/3)c-c | | x+96+21=180 | | 0.96=1.2m. | | 0.2a+8=9 | | 3x+6=3x-8x+7 | | 1/3+2m=-3/2 | | z−9=−12. | | 2x-8x-11=-6x+5-11 | | 2(2+4x)=60 | | 7(x-3)=-28 | | 2(2+4x)=6 | | 6(x+4)=-15 | | H(x)=16x^2+80x | | -5(3-q)+4=5(q-2)+1 | | (11(12+8/15))-8+9y+2=180 | | 7a-12=3a+12 | | 3(4g=6)=2(6g+9) | | 4h^2+28h+49=0 | | 4x-6-5x=2(x+7)-x | | 3x+6=6+3 | | -9(x+4)+3x+7=8x+9 | | -3x+12+11x=5x+33 | | 3x+6=6(x+3)-9 |

Equations solver categories